Najaf à l’heure du pantalon : les enjeux de l’école moderne dans une ville sainte, 1908-1958 - Thibaud Laval (Revue des Mondes Musulmans et de la Méditerranée)
This article examines the development of so-called modern education in the Shiite holy city of Najaf (Iraq) by looking at how the expansion of the educational network allows for the integration of local youth into the nation state. A study of recently published memoirs by Najafis shows that the school plays an eminently political role in developing a militaristic and patriotic culture through sports, history, and theatre. Despite endemic unemployment, the school offers a path to social advancement within the institutions of the new Iraqi state. Although the development of modern education and its symbols, such as trousers, met with strong resistance in Najaf, some ulemas were nevertheless associated with these schools and participated in the secularization of knowledge.